Hemophagocytic lymphohistiocytosis caused by multiple infections during primary chemotherapy for pediatric acute lymphoblastic leukemia: a case report - Ao, Yaning; Huang, Yusheng; Zhou, Xiaobo; Li, Jiawen; Zhang, Qing; Wu, Sujun; Fu, Ying; Zhang, Jinfeng (Frontiers in Immunology, 2024)
Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening hyperinflammatory disorder that occurs as a consequence of immune dysregulation. HLH can be primary (familial or non-familial) or secondary to infection, autoimmune disease or malignancy. Malignancy-associated HLH is often accompanied by hematologic and lymphoid neoplasms. This report describes the case of a 3-year-old girl with an initial diagnosis of acute lymphoblastic leukemia who subsequently developed HLH during primary chemotherapy. She was admitted with a pulmonary infection, and initial blood tests showed thrombocytopenia and anemia. Whole-exome sequencing of gene and whole transcriptome RNA sequencing data indicated mutations of UNC13D. The hospital course was complicated by multiple infections, altered mental status and acute respiratory distress syndrome. HLH secondary to multiple infections that achieved remission following targeted therapy with ruxolitinib, in conjunction with corticosteroids and other complementary treatments. This report provides a synopsis of the diagnostic and treatment procedures implemented in this case.